PENGARUH MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Kurniawan, Hadid; Dwi Kurino, Yeni; Rosidah, Ani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The skill of writing descriptive texts is a crucial competency for elementary school students to master. However, many students still struggle with generating ideas, developing concepts, structuring paragraphs, and using appropriate vocabulary and spelling. Serial image media offers a potential solution to these challenges. This study aims to analyze the impact of serial image media on elementary school students' descriptive writing skills using a Systematic Literature Review (SLR) approach. The research was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review process involved the identification, screening, eligibility assessment, and synthesis of articles based on established inclusion criteria, resulting in the selection of nine relevant articles. The analysis indicates that serial image media has a positive effect on students' descriptive writing skills. The use of serial image media assists students in generating ideas, developing content, structuring paragraphs coherently, and enriching their vocabulary, while also boosting learning motivation and engagement. Furthermore, several studies suggest that the effectiveness of serial image media is enhanced when combined with learner-centered instructional models, such as Think-Talk-Write (TTW), Concept Sentence, and question-and-answer methods. Consequently, serial image media is recommended as an effective tool for improving the descriptive writing skills of elementary school students.